Precious and Grace [large type] - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- No. 1 Ladies Detective Agency series, 2016)
Helping Mr. Polopetsi with an entanglement in a pyramid scheme and Charlie with a dubious romance, an unassisted Precious Ramotswe tackles the case of a young Canadian woman who would find a long-lost acquaintance from her Botswana childhood.